2021
DOI: 10.5435/jaaos-d-21-00091
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Ramp Lesions: Anatomy, Epidemiology, Diagnosis, and Treatment

Abstract: Injuries to the medial meniscus meniscocapsular junction, also known as ramp lesions, are common in the setting of anterior cruciate ligament injuries with a prevalence of 9% to 42%. Anatomically, ramp lesions involve disruption of the posterior meniscocapsular junction and meniscotibial ligaments. Biomechanically, ramp lesions are associated with an increase in anterior tibial translation and internal and external tibial rotation in anterior cruciate ligament-deficient cadaveric knees. Magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Only the repair of meniscal ramp lesions is able to restore anterior and rotational laxity [ 12 , 37 ]. If meniscal ramp lesions are overlooked in patients with ACLR, anterior and rotational laxity persists [ 1 , 7 , 12 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only the repair of meniscal ramp lesions is able to restore anterior and rotational laxity [ 12 , 37 ]. If meniscal ramp lesions are overlooked in patients with ACLR, anterior and rotational laxity persists [ 1 , 7 , 12 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that saucerization with suture stabilization of the peripheral meniscal rim results in fewer degenerative changes compared with total or subtotal meniscectomy. 7 Although a 6-to 8-mm width of the remaining meniscus rims was recommended as an appropriate value in a previous study, 9 the longterm result of saucerization has been shown to be associated with the progression of lateral compartment arthritis in 68.5% of patients. 9 Moreover, Nishino et al 10 reported that the width of the anterior horn, midbody, and posterior horn decreased significantly from 3 to 24 months after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, meniscal ramp lesions, which have also been associated with increased tibial rotation, were not investigated. 3 Despite these limitations, this study may make a case for the consideration of the TFA as a possible predictive measure for ACLR failure based on a robustly powered study sample of matched-pair patients with ACL injuries and graft failure.…”
Section: Discussionmentioning
confidence: 99%